New Straits Times, 01 July 2007 - Chok, Suat Ling (The New Straits Times Press (M) Bhd, 2007)
The Education Minister will be going all out from this month to make co-curricular activities a priority in school as participation among students has not reached the level desired. Minister Datuk Seri Hisyammuddin Hussein tells the new approaches to boost participation and explains why being active outside the classrooms is crucial.